2015
DOI: 10.1149/2.0221509jes
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Electrochemical Properties of a SnO2-Sb Anode Doped with Ni-Nd for Phenol Oxidation

Abstract: A novel Ni-Nd co-doped SnO 2 -Sb anode with macroporous titanium sheet as substrate (mp-Ti/SnO 2 -Sb-Ni-Nd anode) was prepared by modified sol-gel method. The surface morphology, the crystal structure and the valence of the dopants were characterized by SEM, XRD and XPS, respectively. In addition, CV, LSV, EIS, chronoamperometry measurements and accelerated lifetime test were also carried out to study the electrochemical properties and stability of the anodes. The results indicated that mp-Ti/SnO 2 -Sb-Ni-Nd a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…CNTs (>95%, length of 10-30 mm, outer diameter of 20-30 nm) were obtained from Beijing Nachen Technology Co. Other chemicals and materials were similar to our previous research. 28,29 2.2 Preparation of Pd/CNTs-PPy/Ti composite electrode 2.2.1 Pretreatment of meshed Ti. Ti mesh size and its pretreatment method were same as those in our previous research.…”
Section: Chemicals and Materialsmentioning
confidence: 99%
“…CNTs (>95%, length of 10-30 mm, outer diameter of 20-30 nm) were obtained from Beijing Nachen Technology Co. Other chemicals and materials were similar to our previous research. 28,29 2.2 Preparation of Pd/CNTs-PPy/Ti composite electrode 2.2.1 Pretreatment of meshed Ti. Ti mesh size and its pretreatment method were same as those in our previous research.…”
Section: Chemicals and Materialsmentioning
confidence: 99%
“…25 The electrode was prepared by a sol-gel method. 32 Citric acid was mixed with ethylene glycol at 70 C, and then the solution was heated to 90 C. SnCl 4 $5H 2 O and SbCl 3 were added to the solution in a molar ratio of citric acid : ethylene glycol : SnCl 4 -$5H 2 O : SbCl 3 of 130 : 30 : 9 : 1. The sol-gel was obtained by holding the solution at 90 C for 30 min.…”
Section: Electrode Preparationmentioning
confidence: 99%
“…This was later discussed to be a consequence of surface enrichment of Sb [9,14]. Other studies have also reported an enrichment of either Sb or Ni, or both [24][25][26]. Most authors correlate this to surface enrichment.…”
Section: Introductionmentioning
confidence: 97%